Мотивація праці в реструктуризованих сільськогосподарських підприємствах: аналіз та шляхи підвищення - Купалова, Г.І.; Клокар, О.О. (Інститут демографії та соціальних досліджень НАН України, 2007)
На основе результатов выборочных монографических, социологических исследований проанализированы особенности, преимущества и недостатки современных моделей мотивации труда в аграрном секторе экономики Киевской области. Определены основные направления повышения мотивации трудовой деятельности работников в реструктуризированных сельскохозяйственных предприятиях отдельных организационно-правовых форм. The analysis based on the results of selective monographic, sociological researches is made; the peculiarities, advantages and disadvantages of modern models of work motivation in agrarian sector of the economy of Kiev region are discovered. The main trends of increasing of agricultural workers motivation in re-structed agricultural enterprises with different forms of organization and management are determined.